Pluralist perspectives of a literacy policy in the Western Cape Province - Jacobs, Anthea Hydi Maxine (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MEd (Education Policy Studies))--University of Stellenbosch, 2009.